Low-cost ultrasound phantom for image artefact (low-cup) / Leong Sook Sam ... [et al.] - Sook Sam, Leong; Mohamad Yamin, Lyana Shahirah; Tajuddin, Mohd Amirul; Shamsuddin, Nurul Saadiah; Nor Azman, Nurul Dizyana; Supar, Rafidah (2022)
Ultrasound procedures are becoming more challenging over time as diseases become more complex. Before training on a live patient, operators should learn to identify ultrasound artefacts because they can tamper the diagnostic process and thus affect the detection and diagnosis of life-threatening diseases. Simulated training using an ultrasound phantom provides the opportunity for operators to identify ultrasound image artefacts. This study aims to construct a simple, homemade, and low-cost phantom suitable for basic training in ultrasound artefacts identification. Five basic ultrasound image artefacts: posterior acoustic enhancement, posterior acoustic shadowing, mirror image artefact, reverberation artefact, and comet tail artefact were created using materials that can be easily found in daily life. The created ultrasound image artefacts were then categorized by four sonographers from different hospitals to investigate the observer’s agreement. The total cost spent to create the ultrasound image artefact phantom was RM1.45. The Kappa coefficients showed an excellent inter-observer agreement with kappa more than 0.9 (p<0.001). This indicates that the ultrasound artefacts created using this homemade phantom closely resemble the image artefacts that are routinely seen in a clinical setting. With this low-cost homemade ultrasound image artefact phantom, lecturers can effectively teach more learners the process of image artefact formation and identification at a much more reasonable price.